Synthesis, Characterization and Antimicrobial Activity of Imidazole Derivatives Based on 2-chloro-7-methyl-3-formylquinoline - R. H. Parab; B. C. Dixit (E-Journal of Chemistry)
A series of oxazole and thereof imidazole derivatives were prepared from 2-chloro-7-methyl-3-formyl quinoline. The structures of all synthesized compounds were elucidated by elemental, IR, 1HNMR, 13CNMR spectra. Supplementary to these, they were assayed in vitro for their antimicrobial activity; it was revealed that some synthesized derivatives were exhibiting competent biological activity against both gram negative and gram positive bacterial species and fungal microorganisms.